116PLarge scale functional characterization of mutations and their susceptibility to targeted therapy. (7th November 2019) - Barbash, Z; Tarcic, G; Haham, D; Hafzadi, L; Zipor, R; Barth, S; Aizenman, A
Abstract: Background: Extensive use of NGS profiling in precision oncology is uncovering a staggering amount of novel alterations in the sequenced genes. Strikingly, the number of variants of uncertain significance (VUS) increases linearly with the addition of sequenced samples. While some of the VUS are inconsequential mutations many other VUS lead to activation of the proteins and are therefore involved in oncogenicity and may cause drugs resistance. These new activating mutations can also serve as novel drug targets. Methods: We report here a method for functional annotation of these VUS as well as their sensitivity to targeted therapy. The system is based on rapid synthesis of the mutations and expression of the mutated protein together with fluorescently labeled reporters in a cell-based assay. The assay allows the accurate measurement of signaling pathway activation using fluorescence imaging coupled with high content image analysis. This process can also be performed with targeted agents to determine the sensitivity of the mutation. The output of the system is the level of activity of the mutant relative to a mutation with known activity in the same gene. Results: Our results show that this method is able to accurately identify known driver mutations in 10 different oncogenes spanning 4 major cancer associated signaling pathways as well as over 100 different VUS in these genes. We also extend this analysis and show that the method correctly recapitulates differential sensitivity of EGFR mutations to 2 nd and 3 rd generation EGFR inhibitors and that different classes of BRAF mutations differ in response to specific inhibitors. Finally, we establish the importance of concurrent mutations in the response to EGFR inhibitors. Conclusions: Taken together, this system provides crucial information for the development of new targeted agents and establishes an experimental tool both for patient stratification into clinical trials and patient treatment. Legal entity responsible for the study: The authors. Funding: NovellusDx. Disclosure: Z. Barbash: Full / Part-time employment: NovellusDx. G. Tarcic: Full / Part-time employment: NovellusDx. D. Haham: Full / Part-time employment: NovellusDx. L. Hafzadi: Full / Part-time employment: NovellusDx. R. Zipor: Full / Part-time employment: NovellusDx. S. Barth: Full / Part-time employment: NovellusDx. A. Aizenman: Full / Part-time employment: NovellusDx.